Developing Information Work Competence of Future Primary Education Teachers: An Integrative Pedagogical Model - Nilufar Parda Qizi Omonova (Action Research Journal Indonesia (ARJI), 2026)
The rapid digitalization of educational ecosystems has fundamentally transformed the professional profile of primary school teachers. This study aims to develop, implement, and empirically validate a comprehensive pedagogical model for forming information work competence in pre-service primary education teachers within higher education contexts. A sequential explanatory mixed-methods design was employed over two academic years (2024–2026). The study involved 240 pre-service teachers randomly assigned to experimental (n=120) and control (n=120) groups. A validated Information Competence Assessment Tool (ICAT) was administered, complemented by semi-structured interviews, reflective journals, and classroom observation protocols. The instrument validation process, implementation fidelity metrics, and mixed-methods triangulation provide a replicable framework for Central Asian and similar educational contexts. The experimental group participated in a structured 96-hour integrative intervention spanning six pedagogical modules. Quantitative data were analyzed using ANCOVA, paired/independent t-tests, and effect size calculations. Qualitative data underwent thematic analysis with inter-coder reliability verification. The experimental group demonstrated statistically significant gains across all competence dimensions (p<0.001), with a mean post-test score of 85.4 (SD=6.8) compared to 61.8 (SD=7.2) in the control group (η²=0.58, large effect). Pedagogical integration and critical evaluation showed the highest improvement trajectories. Qualitative analysis revealed four dominant themes: increased pedagogical confidence, development of critical information literacy, enhanced collaborative digital practices, and ethical awareness. The proportion of participants achieving high competence levels rose from 13.3% to 53.3% in the experimental group. This study contributes a contextually adapted, empirically validated model that bridges the persistent gap between technical digital skills and pedagogical application in primary teacher education.